1988
DOI: 10.1002/food.19880320814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amadori rearrangement products on the non‐enzymic browning in model systems

Abstract: The AMADORI product was prepared from D-glucose and L-alanine after HASHIBA. The browning process was investigated by determining the absorbance at 520 nm, in aqueous solutions at 110 "C for 5-8 h. Because of the limited access of oxygen and its low solubility in the reaction medium, the browning proceeded after zeroth order kinetics with the maximum browning rate at pH = 8-9. The browning rate remained unaffected by additions of sodium sulphite, rutin. propyl gallate (except when present at high levels), iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In general, two protons were released for each Cu 2+ -ion that was bound (Rendleman & Inglett, 1990). On the other hand, the browning reaction rate in heated solutions of Amadori compounds depended not only on the amounts of Cu and Fe salts added, but also on the valence of the cations (Bertelli et al, 1996) and the pH of the solution (Pokorny et al, 1988).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In general, two protons were released for each Cu 2+ -ion that was bound (Rendleman & Inglett, 1990). On the other hand, the browning reaction rate in heated solutions of Amadori compounds depended not only on the amounts of Cu and Fe salts added, but also on the valence of the cations (Bertelli et al, 1996) and the pH of the solution (Pokorny et al, 1988).…”
Section: Introductionmentioning
confidence: 98%
“…The intensity of the Maillard reaction, also known as the ''non-enzymatic browning reaction", can be quantified by, among other things, the development of color, either visually (Pokorny, Pilkova, Davidek, & Valentova, 1988), by measuring the absorbance at wavelength 420-450 nm or 520 nm (Bertelli, Torregiani, & Bertolo, 1996;Fallico & Ames, 1999;Pokorny et al, 1988) or by calculation of the absorbance index (Gothwal & Bhavadasan, 1992) or extinction coefficient (Brands, Wedzicha, & van Boekel, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the concentration of oxygen may influence both the overall rate of browning and the formation of low molecular weight oxidation products, such as carboxymethyl lysine. Pokorny et al (1988) reported that the replacement of air by nitrogen in model systems containing Amadori products reduced the reaction rate by half.…”
Section: Miscellaneous Factorsmentioning
confidence: 98%
“…The rate of the Maillard reaction has long been reported to increase with increasing pH up to a maximum at $pH 9-10 ( Ashoor and Zent, 1984;Pokorny et al, 1988), depending on the amino acid involved. Bases can catalyse the initial steps of carbonyl-amine reactions by removing a proton from the nucleophile, increasing its nucleophilicity:…”
Section: Phmentioning
confidence: 99%
“…[5,15,16] Moreover, the browning reaction rate studied in heated solutions of Amadori compounds depends not only on the amounts of metal salts added, but also on the valence of the cations, [6,17] and pH of the solution. [18] Since formations of metal complexes are associated with different but unknown MRP ligands, we have explored the ability of several MRPs with known structures to complex with several biologically relevant metal ions. [19] For instance, the importance of copper in human metabolism is its involvement in oxidative processes.…”
Section: Introductionmentioning
confidence: 99%